Study of Caesarean Section using Robson’s Classification at Provincial Public Hospital - Thakur, Murari (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To categorize all pregnant women admitted for delivery at Provincial Public Hospital Janakpurdham according to Robson’s ten group classification and to assess the caesarean section rate and identify the indications contributing to the same.Methods: This is a prospective study conducted at Provincial Public Hospital Janakpurdham for 3 months from 15 th April to 15 th July 2020 .Total of 1536 participants admitted for delivery including 257 undergoing caesarean section were included in the study and were classified according to the Robson’s classification. For each group, demographic and obstetric profile, relative size and its contribution to the overall caesarean rate was calculated. Results: The overall caesarean section rate was 16.7% (257 among 1536 total deliveries). Robson’s Group 5(Previous caesarean section, singleton cephalic, ≥37 weeks) was the major contributor (46%) to the overall caesarean section rate followed by Group 2b (nullipara, singleton cephalic, ≥37 weeks, caesarean section before labor) (15.6%).Conclusion: Induction of labor for Group 2a and 4a should be done and trial for vaginal delivery in previous Cesarean section for Group 5 should be promoted to reduce the caesarean section rate. Study result is limited by lack of labor induction facility at the study site.